ANALISIS PENGARUH PELATIHAN, KOMUNIKASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KEMENTERIAN AGAMA KOTA PANGKALPINANG - Dewi, Fitriarti; Hasianda Tigor, Ryan; Maharani, Yunita (Jurnal Progresif Manajemen Bisnis, 2021)
This thesis entitled in Bahasa Indonesia: “Analisis Pengaruh Pelatihan, Komunikasi dan Lingkungan Kerja terhadap Kinerja Pegawai pada Kantor Kementerian Agama Kota Pangkalpinang”. This research was conducted during pandemic of Covid-19 (April 2021-June 2021) and was carried out with standard health protocol as being announced nationally, such as gathering the data via online and interview nor observation by telecommunication. The research was administrated in City of Pangkalpinang and consists of 100 pages without attachments. The purpose of this study was to determine how strong the influence of the Training, Communication and Work Environment Control toward the dependent variable which is defined as Employee Performance. This study runs by using quantitative data analysis and was using a Multiple Linear Regression Analysis along with Coefficient of Determination. The results of the analysis state that the training variable partially has a positive and significant effect on employee performance with t-count 3,037 > t-table 1,67793 with a significance of 0,004 <0,05, which means that H0 is rejected and H1 is accepted. Another independent variable, namely Communication partially positive and significant effect on employee performance with t-count 2,342 > t-table 1,67793 with a significance of 0,024 <0,05, which means that H0 is rejected and H1 is accepted. The last independent variable is the work environment which also partially has a positive and significant effect on employee performance with t-count 2,745 > t-table 1,67793 with a significance of 0,009 < 0.05, which means that H0 is rejected and H1 is accepted. As Simultaneously, the variables of Training, Communication and Work Environment have a positive and significant effect on Employee Performance with the value obtained F-count 22,935 > F-table 2,81 with sig 0,001 < 0,05. With the coefficient of determination obtained a value of 0,578, which means that the independent variable can explain the dependent variable simultaneously at 57,8%, and the remaining 42,2% is explained by other independent variables that are not used in this study.